2013
DOI: 10.3892/ijo.2013.1856
|View full text |Cite
|
Sign up to set email alerts
|

Increased in vivo angiogenic effect of glioma stromal mesenchymal stem-like cells on glioma cancer stem cells from patients with glioblastoma

Abstract: The presence of glioma stromal mesenchymal stem‑like cells (GS-MSLCs) in tumors from glioma patients has been previously reported. The mechanisms through which these cells function as a part of the glioma microenvironment, however, remain incompletely understood. We investigated the biological effects of GS-MSLCs on glioma cancer stem cells (gCSCs), testing the hypothesis that GS-MSLCs alter the biological characteristics of gCSCs. GS-MSLCs and gCSCs were isolated from different glioblastoma (GBM) specimens ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…These latter may arise from normal progenitors, in analogy with what occurs in Platelet‐Derived Growth Factor (PDGF)‐induced gliomas of the adult or neonatal rat, where a small population of neural stem cells are “recruited” into the glioma and are induced to proliferate . Accordingly, Kong's group has isolated from a single glioblastoma patient a stem cell line with some mesenchymal features (GS‐MSLC) that showed the ability to influence a GSC line by increasing, in vitro, its proliferation, and, in vivo, the size of the formed tumors via an incremented angiogenesis . Our article newly shows that normal stem cells with mesenchymal features and a wide differentiation potential can be isolated both from LGG and HGG, support tumor growth releasing exosomes, and can predict patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…These latter may arise from normal progenitors, in analogy with what occurs in Platelet‐Derived Growth Factor (PDGF)‐induced gliomas of the adult or neonatal rat, where a small population of neural stem cells are “recruited” into the glioma and are induced to proliferate . Accordingly, Kong's group has isolated from a single glioblastoma patient a stem cell line with some mesenchymal features (GS‐MSLC) that showed the ability to influence a GSC line by increasing, in vitro, its proliferation, and, in vivo, the size of the formed tumors via an incremented angiogenesis . Our article newly shows that normal stem cells with mesenchymal features and a wide differentiation potential can be isolated both from LGG and HGG, support tumor growth releasing exosomes, and can predict patient prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, the expression of pro-angiogenic factors, such as bFGF, platelet-derived growth factor-BB (PDGF-BB) and IGF-1, were reduced suggesting that MSCs inhibited the secretion of these factors by the glioma cells. However, another study using glioma stromal mesenchymal stem-like cells (GS-MSLCs), which are MSC-like cells residing in glioma, demonstrated that MSCs are also able to promote angiogenesis (93). Apparently, the source the MSCs are isolated from is an important factor that determines the effect of MSCs in glioma (94).…”
Section: Paracrine Effects Of Stem Cells In Cancermentioning
confidence: 99%
“…To determine whether mitochondrial fission was coupled to enhanced cell division in response to Doxinduced injury, we assessed the content of PCNA. PCNA is expressed in early G1 and S phase of the cell cycle and functions in cell cycle progression, DNA replication, and DNA repair and has previously been used as a marker of cell proliferation [30,31]. There was no difference in PCNA content between groups (1644.00 AE 110.73 vs. 1543.89 AE 120.94, P = 0.562), indicating that Dox does not induce cell proliferation in livers of treated animals, at least 24 h post-treatment.…”
Section: Marker Of Cell Proliferationmentioning
confidence: 99%